AN EFFICIENT CONTROL APPROACH OF VOLTAGE AND FREQUENCY REGULATION IN AN AUTONOMOUS MICROGRID (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
The sustainable development of a nation is highly dependent on remote area electrification, which consists of a majorly decentralized type of load. To fulfill such energy demands, the microgrid is the emerging alternative that utilizes distributed energy sources. Microgrid performance parameters like voltage-frequency regulation, dynamic and steady-state response become very important when it is operating in islanded mode or under load change conditions. In this paper, an improved efficient power control strategy, based on fuzzy gain scheduling of the conventional proportional-integral controller (FGSPI), is proposed for voltage-frequency control in an inverter-based distributed generation unit. The simulation results of the proposed control strategy are compared with the conventional PI controller under aforesaid conditions. The simulation responses show the effectiveness of the proposed control strategy to restore the stability of the microgrid even in islanded conditions. The intelligent and smooth operation of the proposed controller shows better robust performance than the traditional controller in MATLAB/Simulink environment.
Keywords: Microgrid; Islanded operations; Distributed generation; Fuzzy logic and proportional-integral (PI) controller